Virologic breakthrough in a patient with chronic hepatitis B by combination treatment with tenofovir disoproxil fumarate and entecavir - Suzuki F; Sezaki H; Akuta N; Suzuki Y; Kawamura Y; Hosaka T; Kobayashi M; Saitoh S; Arase Y; Ikeda K; Kobayashi M; Watahiki S; et al. (Dove Medical Press, 2014)
Fumitaka Suzuki,1,2 Hitomi Sezaki,1 Norio Akuta,1 Yoshiyuki Suzuki,1 Yusuke Kawamura,1 Tetsuya Hosaka,1 Masahiro Kobayashi,1 Satoshi Saitoh,1 Yasuji Arase,1 Kenji Ikeda,1 Mariko Kobayashi,3 Sachiyo Watahiki,3 Rie Mineta,3 Yukiko Suzuki,3 Hiromitsu Kumada1 1Department of Hepatology, Toranomon Hospital, Tokyo, Japan; 2Okinaka Memorial Institute for Medical Research, Tokyo, Japan; 3Research Institute for Hepatology, Toranomon Branch Hospital, Kawasaki, Japan Abstract: Tenofovir disoproxil fumarate (TDF) is widely used to treat hepatitis B virus (HBV) patients in the USA and Europe. No confirmed report of resistance selection during treatment with TDF in treatment-naïve and nucleoside/nucleotide analog-treated chronic hepatitis B patients has yet been reported. Here, we report for the first time a patient with chronic hepatitis B and cirrhosis who emerged with virologic breakthrough during combination therapy with TDF and entecavir (ETV), against ETV-resistant virus. A 51-year-old Japanese woman with hepatitis B e-antigen (HBeAg), whose genotype was C, received ETV monotherapy continuously followed by TDF and ETV combination therapy, because her HBV DNA levels had been >3.5 log copies/mL. At the start of combination therapy, amino acid substitutions of the reverse transcriptase (rt) gene, rtL180M, rtT184I/M, and rtM204V, were detected. After this, serum HBV DNA decreased to less than 2.1 log copies/mL and remained at this level until 31 months of combination therapy, when it again began to increase. Amino acid substitutions of rtL180M, rtS202G, and rtM204V emerged and were associated with an increase in serum HBV DNA at virologic breakthrough. Long-term therapy with TDF against the ETV-resistant virus has the potential to induce virologic breakthrough and resistance, and careful follow-up should be carried out. Keywords: hepatitis B virus, resistant